Strategi Promosi Pendidikan melalui Media Sosial Instagram dalam Menarik Minat Peserta Didik Baru di Sekolah Menengah Kejuruan Tritech Informatika - Rifqy Ikhsanul Akmal; Fadli Fadli; Beby Karina Fawzeea Sembiring (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2026)
This study examines the role of Instagram as a digital promotional medium in increasing the interest and number of new student applicants at Vocational High School Tritech Informatika, Medan. The study addresses the growing competition among secondary education institutions and investigates how social media–based educational promotion influences school visibility and enrollment decisions. Employing a qualitative descriptive approach, data were collected through observations of Instagram promotional content, in-depth interviews with key informants—including the school principal, public relations staff, educators, parents of graduating students, and surrounding community members—and documentation of digital promotional materials and student admission records. Data were analyzed thematically to identify patterns in promotional strategies and their perceived impacts. The findings indicate that Instagram-based promotion plays a significant role in enhancing public awareness of the school, strengthening its institutional image, and stimulating prospective students’ interest through visually engaging, informative, and consistently managed content. This study contributes to the literature on educational communication by demonstrating the effectiveness of digital school marketing strategies in student recruitment and offers practical insights for vocational schools seeking to optimize social media platforms for sustainable enrollment growth.